Adverse Associations between Visceral Adiposity, Brain Structure, and Cognitive Performance in Healthy Elderly - Isaac, Vivian; Sim, Sam; Zheng, Hui; Zagorodnov, Vitali; Tai, E-Shyong; Chee, Michael (Frontiers in Aging Neuroscience, 2011)
The link between central adiposity and cognition has been established by indirect measures such as BMI or waist-hip ratio. Magnetic resonance imaging (MRI) quantification of central abdominal fat has been linked to elevated risk of cardio-vascular and cerebro-vascular disease. However it is not known how quantification of visceral fat correlates with cognitive performance and measures of brain structure. We filled this gap by characterizing the relationships between MRI measures of abdominal adiposity, brain morphometry and cognition, in healthy elderly. Methods: A total of 184 healthy community dwelling elderly subjects without cognitive impairment participated in this study. Anthropometric and biochemical markers of cardio-vascular risk, neuropsychological measurements as well as MRI of the brain and abdomen fat were obtained. Abdominal images were segmented into subcutaneous (SAT) and visceral (VAT) adipose tissue compartments. Brain MRI measures were analyzed quantitatively to determine total brain volume, hippocampal volume, ventricular volume and cortical thickness. Results: VAT showed negative association with verbal memory (r=0.21, p=0.005) and attention (r=0.18, p=0.01). Higher VAT was associated with lower hippocampal volume (F=5.39, p=0.02) and larger ventricular volume (F=6.07, p=0.02). The participants in the upper quartile of VAT had the lowest hippocampal volume even after adjusting for age, gender, hypertension and BMI (b=-0.28, p=0.005). There was a significant age by VAT interaction for cortical thickness in the left prefrontal region. Conclusions: In healthy older adults, elevated VAT is associated with negative effects on cognition, and brain morphometry.